Role of HRCT in Evaluation of Chronic Suppurative Otitis Media: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In these study 45 clinically diagnosed patients irrespective of age and sex were evaluated in order to determine the role of pre-operative CT scans in chronic otitis media Aim and objective: The aim of this study is to evaluate the usefulness of high-resolution CT scan in depicting the status of the middle ear and surrounding structures in patients suffering from chronic suppurative otitis media and Study the radiological spectrum of chronic suppurative otitis media along with its complication.Result and Conclusion: The HRCT findings showed a high level sensitivity as regards to the presence of cholesteatoma, changes of the ossicular chain, mastoid involvement and erosion of the lateral semicircular canalKeywords: High Resolution Computed Tomography, Cholesteatoma, chronic Otitis Media, Scutum, Ossicular chain